Pancreatic Pseudocyst with Splenic Artery Erosion, Retroperitoneal and Splenic Hematoma - Petre V. H. Botianu; Adrian S. Dobre; Ana-Maria V. Botianu; Danusia Onisor (Case Reports in Surgery)
The erosion of the peripancreatic vascular structures is a rare but life-endangering complication of pancreatic diseases. We report a female patient with a multicompartmentalized pancreatic pseudocyst that eroded the splenic artery resulting in a retroperitoneal and splenic hematoma with hemodynamic instability which required emergency laparotomy with splenectomy, partial cystectomy, ligation of the splenic artery at the level of the vascular erosion, cholecystectomy (lithiasis), and multiple drainage. The postoperative course was difficult (elevated level of platelets, pancreatic fistula) but eventually favourable, with no abdominal complaints and no recurrence at 2-year follow-up. The case shows that the pancreatic pseudocysts may present with acute hemorrhagic complications with life-endangering potential and significant postoperative morbidity.